Risk factors for stunting of under-five children in Myanmar - Oo, Moe Zaw; Soe, Pa Pa (International Journal Of Community Medicine And Public Health, 2023)
Background: This study aimed to identify risk factors and assess their significance concerning childhood stunting in Myanmar. Methods: This study was conducted through the analysis of a secondary dataset based on the 2015-2016 Myanmar Demographic and Health Survey (MDHS 2015-2016), a program funded by the United States Agency for International Development (USAID). Among the 5239 under-five children who participated in the Myanmar DHS 2015-2016 survey, 4172 children with complete anthropometric measurements were included in this study. This was a cross-sectional study, and Chi-squared analysis was applied to determine the association of each risk factor with stunting. In addition, logistic regression was used for multivariate analysis of all risk factors combined. Results: Out of 4172 children who participated in the study, 1146 (27.5%) were stunted. Type of place of residence, household wealth index, and maternal education level have a significant effect on stunting of under-five children with (χ2=52.79, df=1, p=0.000), (χ2=82.03, df=2, p=0.000) and (χ2=72.31, df=3, p=0.000) respectively. When applied to multivariate logistic regression analysis, all three factors remained significant predictors of stunting in under-five children. Conclusions: Individual- and community-level factors determining the stunting of under-five children in Myanmar were explored. Government support programs for the occupation and income of the household heads and household members, as well as education programs targeting women in both the short term and long term, may help improve the condition.